PERANAN LETNAN JENDERAL TNI PURN SYARWAN HAMID DALAM REFORMASI 1998 – 1999 - M Mulya Hendra; Ridwan Melay; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this thesis is to know the role of Lieutenant General TNI Purn Syarwan Hamid in supporting the demands of the students behind the shift of the New Order to the Reform, whereby he served as Vice Chairman of the House of Representatives / Representative representatives of the Armed Forces (FABRI). The aims of this research are: (1) Knowing the life history of Lieutenant General TNI Purn Syarwan Hamid (2) Knowing the role of Lieutenant General TNI Purn Syarwan Hamid in the reform of 1998 - 1999 (3) To find out what ever in the struggle of Lieutenant General TNI Purn Syarwan Hamid for Riau Province when he served as Minister of Home Affairs RI 1998 - 1999 Development Reform Cabinet. The method used in this research is the method of historical research, because this research takes the object of events that occurred in the past. In addition to historical research methods (history), the author also uses biographical analysis techniques, this technique is a method of analyzing one's life history. The results obtained that the role of Syarwan Hamid in reform can be seen in two dimensions. The first dimension concerns Syarwan's political role and choice as the reform movement begins to roll. Second, the role of Syarwan in the position of Minister of Home Affairs Mr. Syarwan Hamid who is the Vice Chairman of the House of Representatives Faction as a person who finalizes the reform movement to achieve political success. Mr. Syarwan also gave the students the opportunity to keep occupying the DPR / MPR building while taking action to discuss accepting student demands In the lead up to the reformation, Pak Syarwan also received the nods of action from various universities in Jakarta to agree on the strategy of occupying the parliament building safely and effectivelyKeywords: Roles, People, Reform, Syarwan Hamid